Health problems in Danish adolescent handball players: Findings from the one-season health and performance promotion in youth sport (HAPPY) study of 945 players aged 11-17 years - Larsen, A. C.; Roos, E. M.; Möller, S.; Juhl, C.; Storm, L. K.; Kongsted, A.; Møller, M. (Scandinavian Journal of Medicine & Science in Sports, 2025)
We aimed to assess the in-season weekly average prevalence proportion, the incidence rate, and burden (the product of incidence rate and duration of injury in weeks) of health problems among Danish youth handball community players aged 11-17. In this 30-week prospective cohort study, players self-reported health problems, including all injuries and illnesses, regardless of time loss or medical attention, and handball exposure using weekly web-based surveys (OSTRC-H2). Sex differences were estimated using Poisson regression (incidence rates) and binomial regression (weekly average prevalence proportions) with clustered robust standard errors. We included 945 players (age: 14.5 ± 1.5 years; 55% female) from 20 clubs across Denmark. The response proportion to the weekly questionnaires was 63% (range: 42%-79%). The average prevalence proportion of health problems was 23% (95% CI 21%-25%), with 17% (95% CI 15%-19%) attributable to injuries and 6% (95% CI 5%-7%) to illnesses. The overall incidence rate was 14.9 (95% CI 13.9-15.9)/1000 h. Female players aged 13-15 showed a higher incidence rate (15.9 [95% CI 14.2-17.8]/1000 h) compared to age-matched males (13.2 [95% CI 11.5-15.1]/1000 h), with an incidence rate ratio of 1.21 [95% CI 1.0-1.4], and had a higher weekly average prevalence proportion (23% [95% CI 19%-27%]) than age-matched males (12% [95% CI 10%-15%]), corresponding to a difference of 10% points [95% CI 6%-15% points]. COVID-19 infection accounted for 36% of reported illnesses. Our findings highlight the need for injury prevention initiatives to address both sudden-onset and gradual-onset injuries in youth handball players. Sex differences in injury measures and the potential link between illness and injury risk warrant further investigation.